Effects of fatigue on postural sway and electromyography modulation in young expert acrobatic gymnasts and healthy non-trained controls during unipedal stance - da Silva, M. C.; da Silva, C. R.; de Lima, F. F.; Rodriguez Lara, J.; Gustavson, J. P.; Magalhães, F. H. (Frontiers in Physiology, 2022)
This study investigated whether expert acrobatic gymnasts respond differentially than their non-trained counterparts during a single-legged stance task performed before and after a protocol designed to induce fatigue in the ankle plantarflexor muscles in terms of (a) postural steadiness and (b) electromyography (EMG) activation. We hypothesized that neuromuscular adaptation due to training would lead to different behavior of center of pressure (COP) and EMG quantifiers after fatigue. Twenty eight female volunteers (aged 11 to 24 years) formed two groups: expert acrobatic gymnastics athletes (GYN, n = 14) and age-matched non-gymnasts [control (CTRL), n = 14]. Fatigue of the ankle plantarflexors (dominant leg) was induced by a sustained posture (standing on the toes) until exhaustion. Traditional COP parameters (area, RMS, mean velocity, and power spectrum at low and high frequency ranges) were obtained with a force plate, and time and frequency-domain EMG parameters were obtained by surface electrodes positioned on the tibialis anterior, soleus, lateral gastrocnemius, medial gastrocnemius, vastus lateralis, biceps femoris, spinal erector and rectus abdominis muscles. The main results showed that fatigue induced a significant increase in postural oscillations in the ML axis (including RMS, velocity and frequency components of the power spectrum), with no significant effects in the AP axis. In terms of postural sway parameters (i.e., COP quantifiers), no superior balance stability was found for the GYN group as compared to CTRL, irrespective of the fatigue condition. On the other hand, the modulation of EMG parameters (in both time and frequency domains) indicated that expert acrobatic gymnastics athletes (as compared to healthy untrained matched controls) used different neuromuscular control strategies to keep their postures on single-legged quiet standing after the fatiguing protocol. The present results improve our knowledge of the mechanisms behind the interplay between fatigue and postural performance associated with the neuromuscular adaptations induced by sport practice. The design of gymnastics training might consider strategies aimed at improving the performance of specific muscles (i.e., tibialis anterior, soleus, biceps femoris, spinal erector) for which particular activation patterns were used by the acrobatic gymnastics to control single-legged quiet standing.